Correct Identification of Ochrobactrum anthropi From Blood Culture Using 16rRNA Sequencing: A First Case Report in an Immunocompromised Patient in Mexico - Aguilera-Arreola, Ma. G.; Ostria-Hernández, Martha L.; Albarrán-Fernández, Enrique; Juárez-Enriquez, Sara R.; Majalca-Martínez, Cristina; Rico-Verdín, Beatríz; Ruiz, Enrico A.; Ruiz-Palma, María del Socorro; Morales-García, María R.; Contreras-Rodríguez, Araceli (Frontiers in Medicine, 2018)
In this report, we describe our experience of misidentifying Brucella spp. from a positive blood culture using traditional microbiology tests, and when a molecular test was used, the bacterium identified was Ochrobactrum anthropi. To the best of our knowledge, this report is the first such case reported in Mexico.